Inpatient rehabilitation outcome: a matter of diagnosis? - Bejor M (Dove Medical Press, 2013)
Maurizio Bejor,1 Francesca Chiara Ramella,1 Elena Dalla Toffola,1 Mario Comelli,2 Matteo Chiappedi31University of Pavia, Department of Surgical, Resuscitative, Rehabilitative and Transplant Sciences, Pavia, Italy; 2University of Pavia, Department of Brain Sciences, Medical Statistics Section, Pavia, Italy; 3Don Carlo Gnocchi ONLUS Foundation, Milan, ItalyBackground: Patients with comorbidities are becoming more and more common in Italian rehabilitative wards. These comorbidities are considered a major problem for inpatient rehabilitation, due to the fact that they cause longer lengths of stay, higher costs, and lower functional results.Methods: To investigate the possible relationships between comorbidity, functional impairment, age, and type of discharge in patients hospitalized in postacute rehabilitation facilities, we planned an observational study. A total of 178 consecutive inpatients (average age: 78 years [range: 39–99]) from postacute rehabilitation facilities were recruited. Primary diagnosis, comorbidity rating (Cumulative Illness Rating Scale – Geriatric version, CIRS-G) and functional impairment score (Functional Independence Measure, FIM™) were evaluated at admission. The FIM™ rating was also assessed at hospital discharge.Results: A total of 178 of the 199 enrolled patients completed the rehabilitation treatment (89.4%). The average length of stay was 46 ± 24 days. CIRS-G showed an average comorbidity score for each patient of 4.45 ± 1.69. The average FIM™ rating was 79 ± 24.88 at admission, and 91.9 ± 25.7 at discharge. Diagnosis at admission (grouped according to the International Classification of Diseases 9-CM) seemed to correlate with functional results, since lower rehabilitative efficiency was obtained for patients who had a history of stroke.Conclusion: The number and type of comorbidities (CIRS-G) in rehabilitation inpatients do not seem to affect functional outcomes of treatment. The determining factor for a lower level of functional recovery seems to be the diagnosis at admission.Keywords: diagnosis, rehabilitation, inpatients, outcome